Persistence of emerging viral fecal indicators in large-scale freshwater mesocosms. (1st December 2020) - Greaves, Justin; Stone, Daniel; Wu, Zhenyu; Bibby, Kyle
Abstract: Fecal indicator bacteria (FIB) are typically used to monitor microbial water quality but are poor representatives of viruses due to different environmental fate. Viral fecal indicators have been proposed as alternatives to FIB; however, data evaluating the persistence of emerging viral fecal indicators under realistic environmental conditions is necessary to evaluate their potential application. In this study, we examined the persistence of five viral fecal indicators, including crAssphage and pepper mild mottle virus (PMMoV), and three bacterial fecal indicators ( E. coli, enterococci and HF183/BacR287) in large-scale experimental ponds and freshwater mesocosms. Observed inactivation rate constants were highly variable and ranged from a minimum of −0.09 d −1 for PMMoV to a maximum of −3.5 d −1 for HF183/BacR287 in uncovered mesocosms. Overall, viral fecal indicators had slower inactivation than bacterial fecal indicators and PMMoV was inactivated more slowly than all other targets. These results demonstrate that bacterial fecal indicators inadequately represent viral fate following aging of sewage contaminated water due to differential persistence, and that currently used fecal indicator monitoring targets demonstrate highly variable persistence that should be considered during water quality monitoring and risk assessment. Highlights: Viral indicator decay was slower than bacterial indicator decay. PMMoV had extended persistence compared to all other indicators. Fecal indicators, except PMMoV, had faster decay in the presence of sunlight. Relative inactivation will help develop each indicator for water quality monitoring.